Memahami Komunikasi Pemasaran Politik - Ibnu Hamad (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
This article explores political marketing communication as a means of political communication using concept and marketing communication techniques to buy political product. According to the goals (such as position, title, and wealth), what considered as political communication products in its broadest terms are leadership, institution, membership, policy, and political activities. Principles, methods, and stages of political communication must be attended seriously so that the product being sold would be embraced by political audience.